IMMUNOHISTOCHEMICAL EVALUATION OF PULMONARY MICROVASCULAR ENDOTHELIUM IN ALLOXAN-INDUCED DIABETES - Dildova R. Sobirova (Central Asian Journal of Medicine, 2025)
This study focuses on the immunohistochemical changes in endothelial cells of lung vessels in experimental diabetes. The increased expression of VEGFA-1 and ICAM1 markers indicates endothelial cell damage, new vessel formation, and activation of the neoangiogenesis process. These markers play a crucial role in assessing damage and inflammation processes, as well as understanding pathological vascularization in diabetes. The findings demonstrate the role of VEGFA-1 and ICAM1 markers in the development of diabetic angiopathy and vascular pathology.